Development and content validation of a structured gymnastics programme to enhance gross motor skills in preschool children - Pradipta, Galih Dwi; Rachmawati, Umi; Maliki, Osa; Widiyatmoko, Fajar Ari; Hudah, Maftukin (UIR Press Bekerjasama dengan International Association of Physical Education and Sports, 2026)
Background: Despite the growing use of gymnastics programmes in early childhood education, most studies emphasise implementation and outcomes rather than the systematic development and rigorous validation of programme content. As a result, many programmes may be applied without sufficient empirical evidence of their appropriateness, limiting their effectiveness in promoting gross motor skill development. Objectives: This study aimed to develop and evaluate the content validity of a structured gymnastics programme designed to enhance gross motor skills in preschool children. Methods: This study employed a research and development (R&D) approach focusing on the content validation stage. The programme was evaluated by five expert validators with backgrounds in early childhood education, physical education, and children’s gymnastics. Content validity was assessed using Aiken’s V index based on expert ratings. Results: The findings indicated that all components of the developed programme achieved Aiken’s V values ranging from 0.80 to 1.00, demonstrating a high level of agreement among experts regarding the relevance, clarity, and appropriateness of the programme content. Conclusion: The results suggest that the developed gymnastics programme has strong content validity and is suitable for supporting gross motor skill development in preschool children. This study contributes by providing a systematically developed and empirically validated programme for early childhood physical education.